2001
DOI: 10.1002/rcm.415
|View full text |Cite
|
Sign up to set email alerts
|

Moving pieces in a proteomic puzzle: mass fingerprinting of toxic fractions from the venom of Tityus serrulatus (Scorpiones, Buthidae)

Abstract: Scorpion venoms are very complex mixtures of molecules, most of which are peptides that display different kinds of biological activity. These venoms have been studied in the light of their pharmacological targets and their constituents are able to bind specifically to a variety of ionic channels located in prey tissues, resulting in neurotoxic effects. Toxins that modulate Na(+), K(+), Ca(++) and Cl(-) currents have been described in scorpion venoms. Mass spectrometry was employed to analyze toxic fractions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 47 publications
2
75
0
6
Order By: Relevance
“…AbNt8 is rich in charged residues, containing 19.7% negatively charged residues (D and E) and 20.9% positively charged residues (R, K and H). Based on the classification rule of NDBPs, AbNt8 was classified as the first member of a new subfamily of NDBPs, NDBP 12 .…”
Section: Novel Types Of Venom Peptides Without Disulfide Bridgesmentioning
confidence: 99%
See 2 more Smart Citations
“…AbNt8 is rich in charged residues, containing 19.7% negatively charged residues (D and E) and 20.9% positively charged residues (R, K and H). Based on the classification rule of NDBPs, AbNt8 was classified as the first member of a new subfamily of NDBPs, NDBP 12 .…”
Section: Novel Types Of Venom Peptides Without Disulfide Bridgesmentioning
confidence: 99%
“…Venomics studies using optimized liquid chromatography mass spectrometry (LC-MS) approaches revealed that each species of scorpions may contain approximately 100 different venom peptides [2,11,12]. It was estimated that approximately 200,000 different venom peptides exist in the venom glands of 2000 different species of scorpions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactive fractions or substances are usually disregarded as they are not expected to yield a valuable end product. These basic considerations have led to the present situation where of 100 -300 distinct polypeptides that can be monitored by mass spectroscopy in the venom of a single scorpion or a spider, the biological activity of only a small portion has been characterized (4,38,39). However, there are numerous reasons to believe that compounds that at first glance seem inactive should not be ignored.…”
mentioning
confidence: 99%
“…It is therefore rational to believe that when scorpion toxins that affect Na v s degrade either in the venom glands (39) or in the stung animal (hemolymph or blood), their partially degraded derivatives may "boost" the impact of the entire venom. This phenomenon also provides a conceptual basis to future attempts to decrease doses of drugs by harmless, allosterically acting compounds.…”
mentioning
confidence: 99%